2020
DOI: 10.1126/sciimmunol.aax0062
|View full text |Cite
|
Sign up to set email alerts
|

Gut-resident CX3CR1 hi macrophages induce tertiary lymphoid structures and IgA response in situ

Abstract: Intestinal mononuclear phagocytes (MPs) are composed of heterogeneous dendritic cell (DC) and macrophage subsets necessary for the initiation of immune response and control of inflammation. Although MPs in the normal intestine have been extensively studied, the heterogeneity and function of inflammatory MPs remain poorly defined. We performed phenotypical, transcriptional, and functional analyses of inflammatory MPs in infectious Salmonella colitis and identified CX3CR1+ MPs as the most prevalent inflammatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(65 citation statements)
references
References 109 publications
0
58
0
Order By: Relevance
“…A recent publication addresses the role of CX3CR1 + cells in induction of tertiary lymphoid structures and IgA response in salmonella colitis and determined a mechanistic requirement of the CX3CR1 HIGH expressing subtype (Koscsó et al 2020). However, while CX3CR1promotor-driven Cre-recombinases were used to assess the role of antigen presentation by this cell type, the study did not address the functional role of the CX3CR1 molecule itself in this process.…”
Section: Systemic Cx3cr1 + Effects With Potential Impact On Kidney Diseasementioning
confidence: 99%
“…A recent publication addresses the role of CX3CR1 + cells in induction of tertiary lymphoid structures and IgA response in salmonella colitis and determined a mechanistic requirement of the CX3CR1 HIGH expressing subtype (Koscsó et al 2020). However, while CX3CR1promotor-driven Cre-recombinases were used to assess the role of antigen presentation by this cell type, the study did not address the functional role of the CX3CR1 molecule itself in this process.…”
Section: Systemic Cx3cr1 + Effects With Potential Impact On Kidney Diseasementioning
confidence: 99%
“…This includes the protective effect of the mucus, 9 , 18 , 19 the secretion of antimicrobial peptides, 20 the recruitment of neutrophils and other inflammatory cell types to eliminate the pathogen, 21 23 and the production of pathogen-specific IgA that accelerates pathogen clearance from the lumen. 24 , 25 In addition, experiments both in vivo and in cultured cells have revealed that inflammasomes, made up of NOD-like receptors (NLRs) and/or inflammatory caspases, are of central importance in the S .Tm-infected mucosa. 26 Several distinct inflammasomes, including canonical NLR/Caspase-1 inflammasomes 27 39 and non-canonical Caspase-11 (Caspase-4/5 in human) inflammasomes 29 , 31 , 40 have been implicated during S .Tm gut infection.…”
Section: Introductionmentioning
confidence: 99%
“…In summary, our study proposes that fecal exosomal smRNA profiling offers a new groundbreaking opportunity to monitor the inflammatory status of the gut with a capability of detecting its pro-inflammatory (asymptomatic) status. IBD is considered to progress slowly with spatiotemporally dynamic interplay of multiple subsets of immune cells (28). Our next step is to understand from which cells these exosomes are secreted and their physiological impact in vivo.…”
Section: Resultsmentioning
confidence: 99%